Trends in Care Practices, Morbidity, and Mortality of Extremely Preterm Neonates, 1993 to 2012. Issue 2 (June 2016) - Stoll, B.J.; Hansen, N.I.; Bell, E.F.; Walsh, M.C.; Carlo, W.A.; Shankaran, S.; Laptook, A.R.; Sánchez, P.J.; Van Meurs, K.P.; Wyckoff, M.; Das, A.; Hale, E.C.; et al.
Abstract : ( JAMA . 2015;314(10):1039–1051) Extremely preterm infants contribute disproportionately to the burden of neonatal morbidity, mortality, and long-term neurodevelopmental disability. This study of extremely preterm infants born at Human Development Neonatal Research Network (NRN) centers is the first comprehensive review to evaluate how care practices, major morbidities, and mortality have evolved over a 20-year period.